The Effect Of Store Atmosphere On Re-Visit Breaktime Interest In Bima City - Fitri Ridwan; Herry Nurdin (Economy Deposit Journal (E-DJ), 2020)
This study aims to analyze the effect of store atmosphere on the interest of revisiting at Bima City Break Time. The type of research used is associative using a quantitative approach. The research variables consist of: store atmosphere (X) and repurchase interest (Y). All variables are measured using a Likert scale. The population in this study was 96 respondents. Testing instruments using the validity test and reliability test. The data analysis tool used is simple linear regression with SPSS version 16. The results show the following regression lines: Y = 7.312 + 0.239X + e. R value (Correlation Coefficient) obtained is 0.359 or 35.9% and R Square value (Coefficient of Determination) is 0.129 or 12.9%. The results in this study indicate that the store atmosphere influences purchasing decisions as evidenced by the value of t arithmetic 3.725> t table 1.985 and a significance value of 0.000 <0.05. Keywords: Store atmosphere, consumer repurchase interest.